In-silico Exploration of Phytoconstituents of Gymnema sylvestre as Potential Glucokinase Activators and DPP-IV Inhibitors for the Future Synthesis of Silver Nanoparticles for the Treatment of Type 2 Diabetes Mellitus - Chavan, Ajinkya; Daniel, Kratika; Patel, Ansar M. (Current Enzyme Inhibition, 2022)
Background: Diabetes has a large death toll worldwide, particularly as it falls into the ten leading causes of death. Type 2 diabetes mellitus (T2DM) occurs as the body becomes resistant to insulin and sugar accumulates in the blood. It has been observed that dipeptidyl peptidase-IV (DPP-IV) inhibitors and glucokinase activators are known therapeutic agents to treat T2DM. Among the possible medicinal plants, Gymnema sylvestre (GyS) belongs to the Apocynaceae family and is traditionally used for the treatment of different diseases. This plant is also known as “Gurmur” because it has a sugarreducing ability. GyS is known to be one of the main botanicals for the treatment of diabetes. Objective: Considering the studies described above, we have tried to investigate the natural DPP-IV inhibitors and potent glucokinase activators from the phytoconstituents of GyS. New drug candidates from the medicinal plant GyS have been reported as potent DPP-IV inhibitors and glucokinase activators. Methods: As a preliminary investigation, we have studied the effectiveness of phytoconstituents of GyS in T2DM through molecular docking as a proof of concept of synthesizing silver nanoparticles (for the treatment of T2DM) using an extract of this plant. Results: The present investigative research shows that the recognized compounds included in the present analysis have important values in the treatment of diabetes mellitus. The nine compounds selected are evaluated on the basis of DPP-IV and glucokinase enzyme binding energy values and their drug properties. Except for quercitol, all the selected compounds have exhibited much more potent glucokinase activation potential than their native ligands. Gymnemasin A, lupeol, gymnemoside A, gymnemasaponin V, and gymnemic acid I have shown excellent DPP-IV inhibitory potential. Conclusion: We aimed to synthesize the silver nanoparticles from the leaf extract of GyS for the treatment of T2DM. As a preliminary investigation, we have studied the effectiveness of phytoconstituents of GyS in T2DM through molecular docking as proof of synthesizing silver nanoparticles (for the treatment of T2DM) using an extract of this plant. As a result of the present investigation, it has been concluded that these compounds can be used to treat T2DM, and hence, in the future, we can synthesize the silver nanoparticles from the GyS extract for the treatment of T2DM.
Keywords: gymnemasin A